New Quests in Stellar Astrophysics II Ultraviolet Properties of Evolved Stellar Populations - Chavez Dagostino, Miguel; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
This book presents an up-to-date collection of reviews and contributed articles in the field of ultraviolet astronomy. Its content has been mainly motivated by the recent access to the rest frame UV light of distant red galaxies, gained through large optical facilities. This driveway has derived in a renewed interest on the stars that presumably dominate or have important effects on the integrated UV properties of evolved systems of the nearby and faraway Universe. The topics included in this volume extend from the fresh spectroscopic analyses of high redshift early-type galaxies observed with the 8-10m class telescopes to the fundamental outcomes from various satellites, from the long-lived International Ultraviolet Explorer to current facilities, such as the Galaxy Evolution Explorer. This is one of the few volumes published in recent years devoted to UV astronomical research and the only one dedicated to the properties of evolved stellar populations at these wavelengths. This contemporary panorama will be an invaluable resource in the preparation of the next planned space missions, such as the World Space Observatory and the Ultraviolet Imaging Telescope.
The Rest-Frame UV Spectrum of Elliptical Galaxies at High Redshift -- Rest-Frame UV and Visible Properties of Early Type Galaxies at 1 #x003C; #x003C; 2 -- Effect of Reionization on High-z Stellar Populations -- Near UV Properties of Early#x2013;Type Galaxies at z #x007E; 1 -- High Redshift Simulations Using the GALEX Ultraviolet Images of Nearby Galaxies -- GALEX Studies of Early-type Galaxies: the UV Rising Flux and Residual Star Formation -- UV Excess and AGB Evolution in Elliptical-Galaxy Stellar Populations -- Binary Stars as the Source of the Far-UV Excess in Elliptical Galaxies -- Stellar Populations in Field Early#x2013;Type Galaxies -- GALEX UV Observations of Elliptical Galaxies in Abell Clusters at z #x003C; 0.2 -- Near-UV Merger Signatures in Early-Type Galaxies -- The Chemical Composition of Elliptical Galaxies Through Mid-UV Indices -- Colours of the Envelopes of cD Galaxies -- A Morphological Study of M81: Comparison Between GALEX and Spitzer Imaging -- The Impact of Encounters on the Members of Local Group Analogs. A View from -- GALEX UV Spectroscopy of Extended Objects: The Case of NGC3079 -- An Atlas of GALEX UV Spectra Selected from the CDFS -- Weak X-ray Galaxies in the Chandra Deep Field South: Searching for an Early Stage of Star Formation -- UV Observations of Galactic Globular Clusters -- Globular Clusters with the Extended Horizontal-Branch as Remaining Cores of Galaxy Building Blocks -- The Blue Straggler Star Radial Distribution: Clues on Formation Mechanisms -- Infant Mortality of Star Clusters: on the Origin of the Diffuse UV Emission -- Are the Compact Star Clusters in M82 Evolving Towards Globular Clusters? -- NGC 4214: Cluster Properties Derived from Multi-band Photometry -- UV Spectroscopic Indices of Galactic Globular Clusters -- The Extended Emission of Ultracompact HII Regions: An Overview and New Observations -- Horizontal Branch Stars and the Ultraviolet Universe -- Subdwarf B and O Stars: Which Evolutionary Pathways? -- Computing Solar Absolute Fluxes -- Recent Progress in Modeling Stellar Atmospheres -- Ultraviolet Stellar and Cluster Spectra Compared to Theoretical Templates -- A Novel Precise Method for Correcting the Temperature in Stellar Atmosphere Models -- New Model Atmospheres: Testing the Solar Spectrum in the UV -- Photoionization, Recombination, and Radiative Transitions of Atoms and Ions -- Recombination rates, Resonance Strengths and Line Profiles of Dielectronic Satellite Lines of He-like Ca, Fe, Ni -- Population Synthesis at Short Wavelengths and Spectrophotometric Diagnostic Tools for Galaxy Evolution -- Constraining Galaxy Evolution With Hubble#x2019;s Next Generation Spectral Library -- Spectral Evolution and Line Strength Indices in the UV -- Synthesis Models in a Probabilistic Framework: Metrics of Fitting -- World Space Observatory-UltraViolet: International Space Mission for the Nearest Future -- The Focal-plane Instruments on Board WSO-UV -- Science with the World Space Observatory - Ultraviolet -- Introducing UVIT -- Efficiency of Selected UV Space Based Spectrometers -- Astronomy at the University of Guadalajara.
Keywords: Physics; Astronomy; Astrophysics; Cosmology; Observations, Astronomical; Astronomy -- Observations; Physics; Astronomy, Astrophysics and Cosmology; Astronomy, Observations and Techniques; Astrophysics and Astroparticles; Electronic books